„Metamorfozy albo Złoty Osioł” Apulejusza jako punkt wyjścia dla spektaklu „Metamorfozy” OPT „Gardzienice” - Kołdrzak, Elżbieta (Collectanea Philologica, 2015)
“Metamorphoses or The Golden As”s by Apuleius as a text involved with the theme of initiation and acquainting with mystery, in itself is a complex and multi-plotted research material. Similarly, the spectacle realised by the Theatrical Practices Centre “Gardzienice”, led by Włodzimierz Staniewski. The main issue discussed in this article is the concept of translating the narration of Apuleius’ novel into a theatrical text and defining it based on the cultural and existential meaning composing the meaning of “Gardzinice”’s spectacle for the dynamics and the directions of modern cultural discourse that from twenty years ago, as well as today’s. Metamorphosis as a study of pragmatic metaphysics, the confrontation of pride of modern reason with the European culture’s “archive,” in its expression not sentimental but full of irony towards the progressing deconstruction of the spiritual-symbolic sphere in contemporary narrations, are a still valid spectacle, becoming even more actual.